Cultural Contexts in Consumer Behavior : A Qualitative Case Study Review of Market Research - Hamdullah Azimi; Mohammad Yusuf Saleh (International Journal of Management Research and Economics, 2025)
Consumer behavior is shaped by cultural contexts, influencing how individuals perceive, purchase, and engage with products and services. While traditional market research primarily relies on quantitative methods, this study highlights the importance of qualitative insights in understanding cultural influences. Through a case study approach, the research examines how cultural values, norms, and traditions impact consumer preferences and brand interactions across various markets. Key findings reveal that collectivist cultures prioritize community and social harmony in purchasing decisions, whereas individualistic cultures focus on personal achievement and self-expression. Additionally, high uncertainty-avoidance societies tend to favor well-established and reputable brands, whereas low uncertainty-avoidance cultures show openness to innovation. Digital globalization has also transformed consumer behavior, with AI-driven marketing and e-commerce platforms fostering hybrid consumer identities that integrate global and local influences. This study provides actionable recommendations for businesses, including adopting culturally adaptive marketing strategies, leveraging AI-driven consumer analytics, and enhancing localized branding efforts. The research contributes to the broader discourse on cultural influences in marketing and consumer engagement, emphasizing the need for businesses to adapt to evolving cultural dynamics in a digitally interconnected world. Future research should further explore the intersection of AI, digital globalization, and cultural adaptation in shaping cross-cultural marketing strategies to enhance business effectiveness in global markets.​